Social Meaning in the “Subuh Berkah” Movement: A Living Hadith Study at Dr. Suud Al-Usaywi Mosque, Tangerang, Banten - Mahmudhatul Lutfiya Khasanah; Muhammad Alif (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to analyze the practice of Subuh Berkah as a form of the actualization of Living Hadith and to interpret community religious actions through Max Weber’s social action framework. The research adopts a Living Hadith approach, employing data collection techniques including observation, in-depth interviews, and documentation related to the Subuh Berkah movement at Dr. Suud Al-Usaywi Mosque, Grand Balaraja Residence, Tangerang, Banten. The findings indicate that the Subuh Berkah movement is a mosque-based initiative encompassing congregational prayer, collective social action, and efforts to enhance community welfare, organized by the mosque management board of Dr. Suud Al-Usaywi Mosque. The results demonstrate that Subuh Berkah represents Living Hadith through the internalization of values associated with the virtues of congregational prayer, circles of religious learning, charity, and Islamic brotherhood. From the perspective of social action theory, this practice embodies value-oriented, goal-oriented, affective, and traditional actions. This study concludes that the Subuh Berkah movement is capable of mobilizing and strengthening social cohesion, religious identity, and communal culture within society. The implications of this research affirm that hadith functions as a living tradition manifested in contextual and sustainable social practices.